LOAN AND RETURN INFORMATION SYSTEM QR CODE-BASED VILLAGE LIBRARY BOOK - Nadiatul Munawaroh; Muhamad Muslihudin (STMIK Pringsewu Lampung, 2022)
The library is a facility that affects current technological advances, the Village Library is a means of supporting learning activities that play an important role in increasing educational goals in the Village Community. Library information system technology using QR codes is very useful compared to using manual or handwritten because several systems in the QR Code are able to handle library services and processes that will become more effective and efficient. However, the “Lisa” Library is located in the Kebumen Village area, Tanggamus still uses manuals so it is still difficult to manage data, and find loan data and books. Lack of borrower's sense of responsibility in using library books and still accurate data so that it is not appropriate. To overcome this problem, a library information system is needed. In the current process of technological development, we want to use the QR Code web. By designing using the Waterfall and Fishbone methods as development so that this educational service can be better